Observation of ψ (3686) → Ω − K + Ξ ¯ 0 + c. c - Ablikim, M; Achasov, MN; Adlarson, P; Afedulidis, O; Ai, XC; Aliberti, R; Amoroso, A; An, Q; Bai, Y; Bakina, O; Balossino, I; Ban, Y; et al. (Springer, 2024)
Using (27.12 ± 0.14) × 108ψ(3686) events collected with the BESIII detector at BEPCII, the decay of ψ(3686) →Ω−K+Ξ¯0 + c.c. is observed for the first time. The branching fraction of this decay is measured to be Bψ3686→Ω−K+Ξ¯0+c.c. = (2.78 ± 0.40 ± 0.18) × 10−6, where the first uncertainty is statistical and the second is systematic. Possible baryon excited states are searched for in this decay, but no evident intermediate state is observed with the current sample size.